Sirtuins: Multifaceted Drug Targets - P. Chakrabarty, S.; Balaram, H.; Chandrasekaran, S. (Current Molecular Medicine, 2011)
Sirtuin (Sir2) proteins being key regulators of numerous cellular processes have been, over the recent past, the subject of intense study. Sirs have been implicated in diverse physiological processes ranging from aging and cancer to neurological dysfunctions. Studies on Sir2s using tools of genetics, molecular biology, biochemistry and structural biology have provided significant insight into the diverse functions of this class of deacetylases. This apart, medicinal chemistry approaches have enabled the discovery of modulators (both activators and inhibitors) of Sir2 activity of diverse chemical structures and properties. The availability of these small molecule modulators of Sir2 activity not only has pharmacological significance but also opens up the possibility of exploiting chemical genetic approaches in understanding the role of this multi-functional enzyme in cellular processes.
Keywords: gene transcription